Analyses of the brown stain on the Parthenon Centaur head in Denmark - Rasmussen, Kaare Lund; Rasmussen, Bodil Bundgaard; Delbey, Thomas; Bonaduce, Ilaria; Kjeldsen, Frank; Gorshkov, Vladimir (Springer, 2024)
In 1688 two sculptural fragments, a head of bearded man and a head of an unbearded youth, arrived in Copenhagen, sent from Athens as a gift to King Christian 5. They were placed in the Royal Kunstkammer, their provenance given as the Temple of Artemis in Ephesos, one of the Seven Wonders of the World. Almost a hundred and fifty years later, in the early 1820’s they were noticed and studied by two scholars independently visiting the Kunstkammer. However, both concluded that the two heads belonged to one of the metopes decorating the south side of the Parthenon temple on the Acropolis in Athens, showing fighting between Greeks and the mythical Centaurs, part man and part horse. In the 1830’s another sculptural fragment, a horse’s hoof, obtained through the German archaeologist and state antiquary of Greece, Ludwig Ross, reached Copenhagen. It was forwarded by the Danish consul to Athens, C.T. Falbe, as a gift to King Christian 8. The inventory reads: ‘… was found on the Acropolis near the Parthenon temple and is supposed to belong to one the Centaurs on the metopes.’ The present paper focuses solely on the head of the Centaur. A brown stain was noticed on the Parthenon marbles as early as 1830 by the British Museum and has ever since eluded a deeper understanding of its genesis despite many investigations and attempts of analyses. A quite similar brown stain can be observed on the Centaur’s head in Copenhagen as well. The present study reports analyses by LA-ICP-MS, SEM–EDX, µXRD, GC–MS, and LC–MS-MS, as well as optical microscopy of five small samples sequestered in 1999 from the Centaur head curated by the National Museum of Denmark. Our analyses show that the brown stain consists of two consecutively added surficial layers of the calcium oxalate minerals whewellite and weddellite. Despite a thorough search using proteomics, we have found no viable organic precursor material for the oxalates. Our results do not solve the mystery of the formation of the brown stain, but they do further qualify the structure and characterization of the brown stain.
Keywords: Parthenon temple; Athens; Brown stain; Centaur head